A study on physical characteristics of dried bio-slurry produced in tropical condition through treatment combination of drying and turning period. Issue 1 (November 2021) - Nuhriawangsa, A M P; Ardika, D; Kartikasari, L R; Hertanto, B S
Abstract: The research aims to evaluate the physical characteristics of dried bio-slurry produced by treatment combination of drying and turning period in tropical conditions. Research material used fixed-dome digester model with a capacity of 12 m 3 and cattle dung from Simmental crossbreed. Physical characteristics of bio-slurry were obtained by combining treatments between drying period (15 and 30 days) and turning period (each turning process in 7 and 10 th day) as follows: T1 (15 days and 7 th day), T2 (15 days and 10 th day), T3 (30 days and 7 th day), T4 (30 days and 10 th day). The chemical compound of fresh bio-slurry was analyzed as initial information. The humidity, temperature, and color data were analyzed using analysis of variance and further analyzed using Tukey's test. Also, the chemical compound and pH used descriptive analysis. The study obtained that the chemical composition of fresh bio-slurry was moisture content (89.53%), C-organic (37.27%), nitrogen (48.92ppm), phosphor (1.71%), potassium (3.89%), and C/N ratio (7.454). Besides, the treatment showed a significant difference (P<0.01) in humidity and color. Temperature dan pH of dried bio-slurry remained constant at 29.10-29.27 0 C and 7 respectively. Therefore, treatment combinations can be applied to make dried bio-slurry as fertilizer in tropical conditions.